(untitled) (Jurnal Destinasi Pariwisata, 2025)
This study aims to analyze the characteristics and motivations of visitors to the Muaya Beach tourist attraction in Jimbaran Traditional Village, Badung Regency. Muaya Beach is one of Bali’s leading coastal tourist destinations, known for its natural beauty, serene atmosphere, and stunning sunsets. However, there are limited academic studies examining who these visitors are and what motivates them to visit. This study used a descriptive quantitative approach, using observation, interviews, questionaires, documentation, and literature review as data collection techniques. Data analysis was conducted using frequency distribution and a Likert scale. The results show that the majority of Muaya Beach visitors are students aged 15–24, single, come with friends, and reside in Badung. They spend 1–2 hours, use motorbikes, and spend less than Rp 100,000. The primary motivations for visiting are escape (4.62) and strategic location (4.52). These results are expected to serve as a reference for more targeted destination management based on the needs and preferences of visitors to the Muaya Beach tourist attraction